Can agent-based simulation models replicate organised crime? - Troitzsch, Klaus G. (Trends in organized crime)
The aim of the paper is to discuss the possibility of using complex software agents in a simulation model in order to represent and analyse the dynamics of certain types of criminal systems via Agent Based Modelling (ABM), in particular Extortion Racket Systems (ERSs). It presents a simulation model and the results of a large number of runs to find out under which parameter constellations governing the normative behaviour of the software agents the model replicates the macro observations in a number of provinces in Southern Italy. Finally the simulation model is applied to analysing strategies and their effect on the behaviour of the agents and the system as a whole.